ADAPTIVE AND RESILIENT LEARNING TECHNOLOGIES IN FORMAL AND INFORMAL EDUCATION: A SYSTEMATIC LITERATURE REVIEW - Riska Meisyi Putri; Sarinah Sarinah; Fatimah Al-Rashid (Scientechno: Journal of Science and Technology, 2025)
This study reviews the use of Mobile-Assisted Language Learning (MALL) and digital storytelling in multilingual education, focusing on research trends, teaching strategies, and their impact on inclusive and effective language learning. A systematic literature review was conducted using peer-reviewed studies published between 2020 and 2025 from major academic databases. The studies were analyzed using thematic coding and comparison. The findings show that MALL and digital storytelling improve learner engagement, motivation, intercultural competence, and language proficiency in diverse linguistic and cultural contexts. These approaches also support personalized learning, collaboration, and the development of critical literacy related to social justice and educational equity. The novelty of this review is its integrated view of mobile learning and digital storytelling as connected teaching approaches in multilingual and multicultural settings. By summarizing recent research, this study shows how technology-based learning supports learner autonomy, flexible learning processes, and inclusive teaching practices. The findings offer practical guidance for educators, policymakers, and instructional designers in developing curricula and professional training suited to multilingual classrooms.